Syncro-Mate B® induces estrus in cows without ovaries - McGuire, W.J.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Syncro-Mate B® was capable of inducing estrous behavior in ovariectomized cows. Lengthening the norgestomet implant period from 9 to 18 days did not prevent estrus. The ability of Syncro-Mate B to induce estrous behavior in ovariectomized cows helps explain the variable conception rates obtained after using this product in intact cows.
Keywords: Beef; Syncro-Mate B®; Estrus